If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 4x = -1x + 7m Combine like terms: 3x + 4x = 7x 7x = -1x + 7m Reorder the terms: 7x = 7m + -1x Solving 7x = 7m + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 7x + x = 7m + -1x + x Combine like terms: 7x + x = 8x 8x = 7m + -1x + x Combine like terms: -1x + x = 0 8x = 7m + 0 8x = 7m Divide each side by '8'. x = 0.875m Simplifying x = 0.875m
| -1.2y+.8=-.76 | | 7x+1=2(2x+2) | | 44+m=35 | | h(t)=-16t^2+122t+10 | | 6x-1=4(x-1) | | 4+m=35 | | .5x+.07=.25x+.57 | | -7/13p=-4 | | x^4-4x^3-30x^2-8x-64=0 | | 4x-2=102 | | -6n+-2=16 | | 5r(8r-5)(5r-1)=0 | | 3+8X= | | 19x-5=11x-21 | | 4x+10=3(2x+5) | | 5(12w+1)= | | 16-3.4d=-8 | | 9+3=612 | | 7x+2=3(3x+1) | | 8n-12=40 | | (7+x)/2+3=12 | | 155*22/31*18/25 | | 5a-12=88 | | 9/8*4/5 | | 12-(4m+4)=3+3m-16 | | 2(x-5)+1=-(x+3) | | 7x-24=54 | | -2*(3x-1)-3=-4 | | -0.5x+4.21=0.3x+8.41 | | 6/7*14/27*9/10 | | x-2/3=5-x/2 | | x+16=100 |